Benjamin Franklin : a man with many jobs - Greene, Carol (Chicago : Childrens Press, 1988)
Traces the life and accomplishments of the printer, philosopher, scientist, inventor, and statesman.
Includes index.
Booklist.
2.9
K-3.
K-3
Keywords: Franklin, Benjamin, -- 1706-1790 -- Juvenile literature; Franklin, Benjamin, -- 1706-1790.; Franklin, Benjamin, -- 1706-1790.; Statesmen -- United States -- Biography -- Juvenile literature; Statesmen; Statesmen -- United States -- Biography